Evaluation of Student Performance based on Bridge Course - N, Geetha; Pareek, Piyush Kumar; GK, Suhas; Soman, Sandhya (International Journal of Computer Sciences and Engineering, 2025)
Performance of the student is evaluated and estimated using various evaluation methods and parameters. Modern evaluation methods can have a tremendous impact on the student performance in their curricula. Some courses in the University curriculum has some prerequisites for particular courses and one such course in the University is Data Structures of computer science stream. Students haven’t studied C programming as a prerequisite for this course and the test has been conducted. The results of this test are not satisfactory and hence a bridge course is introduced to overcome the problem of prerequisite and also the pre-test for C programming is also taken for future analysis. The bridge course is conducted for 30hrs in a laboratorysince C is a programming course and post-test is conducted for both the courses. The improvement in results is identified and the performance of studentsis calculated. This research has been conducted on 58 students in the University, the null hypothesis is usedand performed t-Test distribution to analyze the performance of students. This paper tells how a bridge course is useful for the students to perform better and suggests the best suited methods for capturing and analyzing data by choosing the right metrics and performance indicators.